2017
DOI: 10.1136/openhrt-2016-000539
|View full text |Cite
|
Sign up to set email alerts
|

On-X versus St Jude Medical Regent mechanical aortic valve prostheses: early haemodynamics

Abstract: ObjectiveWe aimed to compare the early haemodynamic data of the On-X and St Jude Medical (SJM) Regent bileaflet mechanical prostheses in the aortic position.MethodsA retrospective study was performed using data collected prospectively for a national database. Thirty-three patients who had aortic On-X valve (On-X group) and 33 matched patients who had aortic SJM Regent valve (SJM group) were included. The intraoperative and early postoperative data were collected. The same echocardiographer reviewed all the ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…The values obtained in this in vitro study fall within the range of those obtained in vivo. Xu and colleagues 32 showed in a population study, that regardless of the size of the valve and the diversity of the patients, On-X valves yielded equal or higher EOAs. From a design perspective, the On-X valve is characterized by a larger internal diameter (21.4 mm) compared with the same tissue annulus diameter and valve size SJM (18.6 mm) (Figure 1, A).…”
Section: Effect Of Valve Design On Hemodynamic Parametersmentioning
confidence: 99%
“…The values obtained in this in vitro study fall within the range of those obtained in vivo. Xu and colleagues 32 showed in a population study, that regardless of the size of the valve and the diversity of the patients, On-X valves yielded equal or higher EOAs. From a design perspective, the On-X valve is characterized by a larger internal diameter (21.4 mm) compared with the same tissue annulus diameter and valve size SJM (18.6 mm) (Figure 1, A).…”
Section: Effect Of Valve Design On Hemodynamic Parametersmentioning
confidence: 99%
“…The bileaflets which have achieved long-term clinical application, especially the St. Jude and Carbomedics bileaflets, constitute more than 70 percent of clinical valve types and are recognized as the most excellent artificial mechanical heart valves (7)(8)(9). Most previous studies are case report, or only reported short-term clinical effects.…”
Section: Introductionmentioning
confidence: 99%
“…Each group had 33 patients, and they found no difference in postoperative peak gradient across the prosthesis in both groups. However, for the valve size 25 mm, On-X valves had a lower peak gradient but no difference in the effective orifice area [ 5 ] . We found a similar finding where there was a nonsignificant trend towards lower mean pressure gradient in the 25 mm On-X valve size compared to 24 mm ATS and Bicarbon valve sizes ( P =0.09), as depicted in Figure 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The ideal prosthetic valve is yet to be developed, and several studies showed comparable outcomes among the new generation of mechanical valves [ 5 , 6 ] . Recently, we started to increasingly use the On-X aortic prosthesis due to the advantage of lower anticoagulation targets.…”
Section: Introductionmentioning
confidence: 99%